Analysis of the Influence of Excavated Soil Sand Characteristics on the Rheological and Mechanical Properties of Hydraulic Mortars - Lara Saad; Mustapha Nouri; Mahfoud Tahlaiti; Abdelhafid Khelidj; Julien Fruchet; Prannoy Suraneni (Buildings)
This work investigates the effects of substituting natural sand with excavated soil sand in the formulation of hydraulic mortar developed from a self-compacting concrete (SCC). Four excavated soil sand deposits were studied to assess their physicochemical properties. Subsequently, a reference mortar (RM) was designed using the concrete equivalent mortar method. Furthermore, the effect of incorporating 30% of excavation soil sand under different moisture conditions (natural storage conditions, dry and saturated surface dry state) on the properties of mortar is studied. Spreading tests were carried out to observe how the rheological properties evolve over time. The study includes compressive and flexural strength tests at 2, 7, 14 and 28 days. The results showed that some sands had densities similar to those of natural alluvial sand, while others had lower densities. Water absorption values varied considerably from one sand to another, with some showing values ranging from 1% to 6%, while other sands had values of up to 10%. The results of spreading tests indicate that mortar made with sand in a saturated dry-surface state is more fluid than mortar made with sand in a dry state. Under all conditions, all mortars lose their fluidity over time. The variation in compressive strength among all excavated soil sand mortars compared to the reference mortar remained below 10% at 2 and 28 days, except for one sand with a high clay content. The incorporation of excavated soil sand at this percentage as a substitute for river sand led to an enhancement in the flexural strength of the mortar, with improvements of 40% and 50% observed for certain types of excavated sand. The statistical study revealed a strong relationship between the properties of the sand (in particular, the fines content and their nature, as well as the sand skeleton) and its saturation state, the flowability and the compressive strength of the mortar.